Faktor Produksi Usaha Ternak Itik Petelur Semi Intensif Di Kabupaten Jember - Hariadi Subagja; Budi Prasetyo; Heny Nurjanah (Politeknik Negeri Jember, 2017)
The Research Was Aimed To Know Factors That Influence And Dominant To Egg Layer Duck Bussiness Of Semi-Intensive Poultry Farm In Jember. The Method Used Is Survey Method With 30 Respondents Semi-Intensive Duck Breeders. The Result Of Data Processing Using Multiple Linier Regression Can Be Acquired Aquation:Â From The Equation Means That For Every Unit Of Egg Production Will Be Affected By X1 (Age Of Ducks) Of -15,376, X2 (Feed) Of 0,001, X3 (Medication) Of 0,061, X4 (Employee) Of -0,013, X5 (Fuel) Of -0,022, X6 (Density Of Cage) Of -192,147, And X7 (Long Of Free-Range) Of -410,626. Can Be Concluded Employee Factor Have A Major Influence On The Production Of Duck Eggs. Result Of Calculation Of The Coefficient Of Determination Is 76,5% And The Remaining 23,5% Is Explained By Other Variables Not Included In This Research.Â Keywords : Ducks, Semi-Intensive, Production Factors, Multiple Linier Regression Analysis